AGRARIS : The Efforts for Productivity and Income Improvement of Rice Farming Through the Use New Superior Variety (Case Study) - Eni Istiyanti, Diah Rina Kamardiani (Fakultas Pertanian UMY, 2017)
efficiency, inpari,paddy,productivity